Current dietary recommendations for patients with cystic fibrosis - Stefańska, Katarzyna; Jakimiec-Komisarczyk, Monika; Terlecka, Paulina; Makuch, Marcelina; Jakimiec, Joanna; Igras-Kołdyj, Magdalena; Szczyrek, Michał; Kieszko, Robert; Zwolak, Agnieszka; Milanowski, Janusz; Łuczyk, Robert Jan (Journal of Education, Health and Sport, 2019)
Cystic fibrosis (CF) is classified as metabolic and multisystem disease with autosomal recessive inheritance caused by mutations in the gene located on chromosome 7 encoding cystic fibrosis transmembrane conductance regulator (CFTR) protein. CFTR is a transmembrane chloride channel of epithelial cells and affects the activity of the mucous membrane of the sweat glands, airway epithelium, pancreatic ducts, vas deferens, bile ducts and intestines. In CF, increased concentration of chlorides in the sweat, pancreatic insufficiency and impaired absorption are observed as well as changes in the respiratory system related to, among others, impaired airway patency, weakening of the mucociliary clearance mechanism and the development of bacterial infections. CF is a chronic condition requiring comprehensive therapy. Nutritional treatment is an essential element of CF therapy. Malnutrition is a common complication in patient with CF and eating disorders. The majority of patients with CF have higher energy, protein and fat needs. In addition, supplementation with enzyme preparations, vitamins, sodium chloride, as well as the use of high-energy nutrients is recommended. The aim of the study was to evaluate current nutritional recommendations of patients with CF.